Gen Z’s Knowledge of Halal Foods and Products on Purchase Behaviour - Purnasari, Nurwulan; Astuti, Septin Puji; Rusdan, Ilzamha Hadijah (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
Consuming or utilizing products derived from the pig is forbidden for Muslims. This study describes Islamic university students' understanding of pig derivative products of food and non-food products. This research was conducted by using a questionnaire to collect data. The indicators used in this data are information about various types of products, forms in pig terms, and indicators of product purchasing decisions. The sample used in this study amounted to 350 respondents. Overall, Islamic University students stated that the status of pig derivative products, both food and non-food, is haram. This study shows a relationship between organizations students follow and their knowledge of pig derivative products. However, this is unfollowed by their behavior when buying non-food products. They do not consider the halal status of non-food products except cosmetics products. This result can be valuable information in further halal awareness studies. Gen Z has to increase their knowledge about pig products and their derivatives daily. This result implies that halal knowledge will lead consumers to be more selective in choosing products and suggest institutions or governments socialize halal awareness and education through halal courses or halal training.